Prolonged Laccase Production by a Cold and pH Tolerant Strain of Penicillium pinophilum (MCC 1049) Isolated from a Low Temperature Environment. (9th March 2014) - Dhakar, Kusum; Jain, Rahul; Tamta, Sushma; Pandey, Anita
Abstract : Production of laccase by a cold and pH tolerant strain of Penicillium pinophilum has been investigated under different cultural conditions for up to 35 days of incubation. The fungus was originally isolated from a low temperature environment under mountain ecosystem of Indian Himalaya. The estimations were conducted at 3 temperatures (15, 25, and 35°C), a range of pH (3.5–11.5), and in presence of supplements including carbon and nitrogen sources, vitamins, and antibiotics. Optimum production of laccase was recorded at 25°C (optimum temperature for fungal growth) and 7.5 pH. The production of enzyme was recorded maximum on day 28 (11.6 ± 0.52 U/L) following a slow decline at day 35 of incubation (10.6 ± 0.80 U/L). Fructose and potassium nitrate (0.2%) among nutritional supplements, chloramphenicol (0.1%) among antibiotics, and folic acid (0.1%) among vitamins were found to be the best enhancers for production of laccase. Relatively lower but consistent production of laccase for a longer period is likely to be an ecologically important phenomenon under low temperature environment. Further, enhancement in production of enzyme using various supplements will be useful for its use in specific biotechnological applications.